DESIGN OF INTERNAL AUDIT INFORMATION SYSTEMS OF OCCUPATIONAL SAFETY AND HEALTH MANAGEMENT SYSTEMS - Rohmat Fais Sahhal Hafidhuddin; Indri Santiasih; Wibowo Arninputranto (Journal of Vocational Health Studies, 2025)
Background: The internal audit assessment of the Occupational Safety and Health Management Systems (OSHMS) in the container terminal company currently uses semi-digital forms. The company’s existing audit forms used general data processing software (Microsoft Excel), which was ineffective and inefficient in fulfilling the internal audit assessment of OSHMS. It also needed to be adjusted, referring to the guidelines of the Republic of Indonesia Government Regulation Number 50 of 2012. Digitalization through information systems is recommended to improve the effectiveness and efficiency of the internal audit assessment of OSHMS in the company. Purpose: To analyze the requirements for the internal audit information systems of OSHMS in the company. Method: This study used the direct test method to determine the function of features and menus on the information systems interface and usability testing to determine the percentage of system usability for users. Descriptive analysis was used to identify the requirements for the internal audit information systems of OSHMS in the company. Result: Based on the study conducted, there were minor adjustments to the forms of internal audit of OSHMS in accordance with current regulations. The fulfillment of 166 audit criteria for internal audits of OSHMS at the advanced level in the company required 99 documents of audit evidence. The direct test results show that the information systems function is running according to the study objectives. The results of the usability testing obtained a percentage of 83.15%. Conclusion: The internal audit information systems of OSHMS can be implemented and provide benefits for the company.